Digital Transformation in Action Examining the Reality of Smart City Implementation Journey - Putri Devi Febryanti, Ayu; Sri Darma, Gede (Journal of Law, Politic and Humanities, 2024)
Digital transformation in government governance is one of the main strategies for increasing the efficiency and quality of public services. The smart city concept is present as an innovative solution in facing various urban challenges by utilizing digital technology. This research aims to analyze the implementation of the Electronic Based Government System (SPBE) as a policy in supporting smart cities in Klungkung Regency and identify factors that hinder its implementation. The research method used is a qualitative approach using interview, observation and documentation techniques. The research results show that although SPBE has been implemented to support the integration of government services, there are still significant obstacles, especially in the aspects of infrastructure and human resource readiness. The geographical constraints of Klungkung Regency, which consists of land and islands, also pose a challenge in equalizing digital access. By improving infrastructure, strengthening human resource capacity, and optimizing policy coordination between the central and regional governments, it is hoped that the implementation of smart cities in Klungkung Regency can run more effectively and sustainably.